The Correlation between depression and obesity in children and adolescents - Błażowska, Olga; Naziri, Amir; Styczyńska, Maria; Chyl, Julianna; Kowalewski, Łukasz; Nowak, Weronika; Gutowska, Oliwia; Kostuch, Wiktoria; Zimon, Agata; Jurewicz, Alicja (Quality in Sport, 2026)
BACKGROUND. Obesity and depression are both major problems of health in almost whole world. Moreover, it is predicted that population of patients of mentioned diseases are going to growth. While these conditions are becoming bigger problem, it is important to mark their impact on childen. Results of illnesses in childhood are associated with many longlasting complications. AIM. The aim of this review was to evaluate the bidirectional relationship of depression and obesity in children and adolescents and to underline their influence on health and proper development. Moreover authors were aiming to highlight the importance of physical activity and appropriate diet in the prevention and treatment of mentioned diseases. MATERIAL AND METHODS. A narrative review of the available literature was conducted. PubMed and Google Scholar databases were used for the research. The following keywords were searched: „depression“, „children“, „obesity“, „anxiety“, „adolescent“, „biological mechanisms“, „depressive episode“, „lifestyle“. RESULTS. There are many common factors occuring in pathophysiology of obesity and depression. It is important to underscore that patients require treatment involving both illnesses and they should not be treated separately. Parents play a crucial role during treatment and they have to teach their children healthy habits. Healthy lifestyle is essential in treating these conditions. CONCLUSIONS. Prevention should be the main focus for medical professionals treating obesity and depression. It is important to observe and react in early stages of mentioned conditions. Studies also show the important role of parents and lifestyle education and their impact on development of illnesses.